Slope Undercurrent in the Northwestern South China Sea Beneath the Winter Western Boundary Current - Shen, Junqiang; Fang, Wendong; Li, Li; Qiu, Yun; Xiao, Zheng; Zhang, Junpeng; Guo, Xiaogang (Frontiers in Marine Science, 2022)
We herein report the observation of a slope undercurrent beneath the winter western boundary current of the northwestern South China Sea (SCS), and its spatiotemporal variation. The possible underlying dynamics are also discussed. In situ observations reveal that the northeastward undercurrent is located above the upper slope with a core velocity exceeding 20 cm/s, which extends from 200 m to 800 m in depth with a width of 30–50 km and an along-slope length of approximately 200 km in deep winter of 2006-2007, and is characterized with interseasonal and interannual variabilities. The existence of this undercurrent is also supported by Hybrid Coordinate Ocean Model (HYCOM) results. We find that the slope undercurrent is probably driven by the along-slope pressure gradient associated with the sea level set-up off the continental slope of south Hainan Island and modulated by mesoscale eddies and Rossby waves that propagating from the east. This study will renew our knowledge of the deep slope currents in the northwestern SCS.